Microwave-Assisted Synthesized ZnO@APTES Quantum Dots Exhibits Potent Antibacterial Efficacy Against Methicillin-Resistant Staphylococcus aureus Without Inducing Resistance - Du F; Niu J; Hong Y; Fang X; Geng Z; Liu J; Xu F; Liu T; Chen Q; Zhai J; Miao B; Liu S; et al. (International Journal of Nanomedicine)
Fangyuan Du,1,* Jingqi Niu,1,* Yu Hong,1 Xue Fang,2 Zhihui Geng,1 Jing Liu,1 Fangqi Xu,1 Tingshu Liu,1 Qifan Chen,1 Jingbo Zhai,3 Beiliang Miao,4 Shiwei Liu,4 Yi Zhang,1 Zeliang Chen1 1Key Laboratory of Livestock Infectious Diseases, Ministry of Education, and Key Laboratory of Ruminant Infectious Disease Prevention and Control (East), Ministry of Agriculture and Rural Affairs, College of Animal Science and Veterinary Medicine, Shenyang Agricultural University, Shenyang, 110866, People’s Republic of China; 2College of Animal Husbandry & Veterinary Medicine, Jinzhou Medical University, Jinzhou, 121001, People’s Republic of China; 3Key Laboratory of Zoonose Prevention and Control at Universities of Inner Mongolia Autonomous Region, Medical College, Inner Mongolia Minzu University, Tongliao, 028000, People’s Republic of China; 4Department of Nephrology and Endocrinology, Wangjing Hospital, Chinese Academy of Chinese Medical Science, Beijing, 100102, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Zhang; Zeliang Chen, Key Laboratory of Livestock Infectious Diseases, Ministry of Education, and Key Laboratory of Ruminant Infectious Disease Prevention and Control (East), Ministry of Agriculture and Rural Affairs, College of Animal Science and Veterinary Medicine, Shenyang Agricultural University, 120 Dongling Road, Shenyang, 110866, Liaoning, People’s Republic of China, Email 2005500042@syau.edu.cn; chenzliang5@mail.sysu.edu.cnBackground: Antibiotic resistance of many bacteria, including Methicillin-resistant Staphylococcus aureus (MRSA), has become a major threat to global health. Zinc Oxide Quantum dots (ZnO-QDs) show good antibacterial activity, but most of them are insoluble in water, limiting their application range, and there is a lack of research on drug resistance inducement.Methods: The water-soluble zinc oxide quantum dots modified by APTES (ZnO@APTES QDs) were prepared by a microwave assisted synthesis. Then ZnO@APTES QDs were characterized through various methods. After confirmation of synthesized ZnO@APTES QDs, its bactericidal effect on MRSA was detected through in vitro and in vivo experiments, and its mechanism of action was analyzed.Results: Characterization analysis revealed that the ZnO@APTES QDs have a particle size of 5 nm. The minimum inhibitory concentrations (MIC) were determined to be 64 μg mL− 1 for Escherichia coli (E. coli) and 32 μg mL− 1 for MRSA. The ZnO@APTES QDs showed significant inhibition of MRSA biofilm formation and effectively disrupted mature biofilms. Notably, the ZnO@APTES QDs did not induce tolerance or resistance even after 30 days of repeated exposure, whereas antibiotics led to a rise in bacterial MIC within 3 days and a 60-fold increase after 30 days. Mechanistic analysis indicated that the positively charged quantum dots interact with bacterial surfaces, altering membrane fluidity. Once inside the bacteria, the ZnO@APTES QDs generate reactive oxygen species (ROS), causing DNA damage and bacterial cell death. Moreover, the ZnO@APTES QDs possessed good biocompatibility and demonstrated significant therapeutic efficacy against drug-resistant bacterial infections in both macrophage and mouse wound infection models.Conclusion: In summary, we have synthesized a highly effective water-soluble ZnO@APTES QDs that shows strong antibacterial and therapeutic efficacy against MRSA and other bacteria. The ZnO@APTES QDs holds significant potential for development as a new treatment agent for combating antibiotic-resistant infections. Keywords: water-soluble, antibiotic resistance, biofilm, reactive oxygen species, wound